Temporary help work: Compensating differentials and multiple job-holding - Sarah Hamersma; Carolyn J. Heinrich; Peter R. Mueser (Institute for the Study of Labor (IZA), 2012)
Temporary Help Services (THS) employment has been growing in size, particularly among disadvantaged workers, and in importance in balancing cyclical fluctuations in labor demand. Does THS employment provide some benefits to disadvantaged workers, or divert them from better jobs? We investigate whether THS jobs pay a compensating differential, as would be expected for relatively undesirable jobs. We also address multiple job-holding, exploring whether workers get stuck in THS jobs. We find lower quarterly earnings at THS jobs relative to others, but a 1 per hour wage premium. We reconcile these findings by examining hours worked at THS and traditional jobs.
Keywords: J3; J4; 330; temporary employment; compensating differential; quarterly earnings; wages; multiple jobs; Befristeter Arbeitsvertrag; Niedriglohn; Nebentätigkeit; Ungeschützte Beschäftigung; Lohnstruktur; Schätzung; USA